2014
DOI: 10.1063/1.4866701
|View full text |Cite
|
Sign up to set email alerts
|

A site-selective antiferromagnetic ground state in layered pnictide-oxide BaTi2As2O

Abstract: The electronic and magnetic properties of BaTi 2 As 2 O have been investigated using both the first-principles and analytical methods. The full-potential linearized augmented plane-wave calculations show that the most stable state is a site-selective antiferromagnetic (AFM) metal with a 2 × 1 × 1 magnetic unit cell containing two nonmagnetic Ti atoms and two other Ti atoms with antiparallel moments. Further analysis to Fermi surface and spin susceptibility shows that the site-selective AFM ground state is driv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…Due to the Fermi surface (FS) nesting, the AFM fluctuations develop at Q s = (π, 0, π) and (0, π, π), consistently with the previous theoretical studies [28,29] and the NMR study [22]. Remarkably, we find that the strong orbital fluctuations at q = (0, 0, 0) are induced by the Aslamazov-Larkin vertex correction (AL-VC), which is neglected in the RPA.…”
Section: Introductionsupporting
confidence: 61%
“…Due to the Fermi surface (FS) nesting, the AFM fluctuations develop at Q s = (π, 0, π) and (0, π, π), consistently with the previous theoretical studies [28,29] and the NMR study [22]. Remarkably, we find that the strong orbital fluctuations at q = (0, 0, 0) are induced by the Aslamazov-Larkin vertex correction (AL-VC), which is neglected in the RPA.…”
Section: Introductionsupporting
confidence: 61%
“…[27][28][29][30][31] Many attempts have been made to identify the DW phase in the titanium oxypnictides. Electronic structure models predict a highly anisotropic Fermi surface with box-like electron and hole pockets that are quite well nested and therefore susceptible to either SDW or CDW instabilities [32][33][34][35][36][37][38] . The calculations indicate that strong electron-phonon coupling could induce a superlattice distortion and accompanying CDW.…”
Section: Introductionmentioning
confidence: 99%
“…Anomalies in the temperature dependence of resistivity ρ(T ) and magnetic susceptibility χ(T ) at low temperature are sometimes observed in these systems, getting into an argument over if the anomalies can be attributed to the emergence of charge density waves (CDW) or spin density waves (SDW). [1,2,[4][5][6] Several DFT studies applied to BaTi 2 As 2 O and BaTi 2 Sb 2 O [21][22][23] have reported the possibility of SDW, while it has not yet been observed experimentally, such as by NMR/NQR for Sb 121/123 and µSR for BaTi 2 As 2 O and BaTi 2 Sb 2 O. [16][17][18] Focusing on CDW, the nesting of Fermi surface matters, which is enhanced by 2D nature of Ti 2 O planes.…”
mentioning
confidence: 99%